ESSENCE OF EDUCATION AND EDUCATION IN SOCIETY DEVELOPMENT - Sh. K. Alimov (Bright Mind Publishing, 2025)
Thoughts on the nationalism underlying the processes in New Uzbekistan are discussed.
Keywords: New Uzbekistan, reforms, education and upbringing.